MODERN ART: INTEGRATING SOCIO-AFFECTIVE STRATEGY TO ENHANCE INDONESIAN AND THAI STUDENTS’ INTERACTION IN THE CLASSROOM - Wahyu Mustikasari, Rr. Dewi (Vision: Journal for Language and Foreign Language Learning, 2015)
There were some obstacles which happened in my Writing 1classses due to the languages that were being used for communica-tion, and my Indonesian and Thai Students’ were not communica-tive to interact in the classroom. In this paper, I propose the inte-gratation of socio-affective strategy to boost my Indonesian andThai Students’ interaction that can be facilitated by using modertart. Modern art has several interesting points namely it may displaythe real-world activities, use communicative language, foster persua-sive communication, facilitate student to use their socio-affectivestrategy, and provide integrated skills.